2002
DOI: 10.1093/ajcn/76.6.1446
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and attainment of peak bone mass among peripubertal Finnish girls: a 3-y prospective study

Abstract: Pubertal girls with hypovitaminosis D seem to be at risk of not reaching maximum peak bone mass, particularly at the lumbar spine. Dietary enrichment or supplementation with vitamin D should be considered to ensure an adequate vitamin D status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
200
2
5

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 295 publications
(230 citation statements)
references
References 38 publications
20
200
2
5
Order By: Relevance
“…Low calcium intake is known to increase the efficiency of calcium absorption in adolescents. (46) One possible explanation would be that this adaptive mechanism, because it depends on 1,25-dihydroxyvitamin D 3 [1,25(OH) 2 The proposed threshold of 40 nmol/L for serum 25(OH)D levels to enable optimal lumbar spine mineralization during late puberty, even in low-calcium, low-dairy-product conditions, is similar to thresholds proposed earlier for optimal bone mass accrual during growth: 25 TO 30 nmol/L (9,10,13,35,36) or 40 to 50 nmol/L. (10,11) Given the small size of the subgroup with low calcium and low 25(OH)D levels, it was not possible to single out the negative impact of low 25(OH)D levels from that of other factors associated with winter-spring (eg, lower ultraviolet light energy, qualitative difference in sport activities, or diet).…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…Low calcium intake is known to increase the efficiency of calcium absorption in adolescents. (46) One possible explanation would be that this adaptive mechanism, because it depends on 1,25-dihydroxyvitamin D 3 [1,25(OH) 2 The proposed threshold of 40 nmol/L for serum 25(OH)D levels to enable optimal lumbar spine mineralization during late puberty, even in low-calcium, low-dairy-product conditions, is similar to thresholds proposed earlier for optimal bone mass accrual during growth: 25 TO 30 nmol/L (9,10,13,35,36) or 40 to 50 nmol/L. (10,11) Given the small size of the subgroup with low calcium and low 25(OH)D levels, it was not possible to single out the negative impact of low 25(OH)D levels from that of other factors associated with winter-spring (eg, lower ultraviolet light energy, qualitative difference in sport activities, or diet).…”
Section: Discussionsupporting
confidence: 59%
“…(9)(10) But the consequences of low 25(OH)D levels are less clear on trabecular bone sites, such as hip, upper femur, and lumbar spine. (8,9,12,13) At the lumbar spine, one longitudinal observational study (13) and two randomized, placebo-controlled studies (42,43) suggest that low 25(OH)D levels may impair bone mass acquisition during the early phase of puberty, but not in girls with more advanced sexual maturation. In contrast, numerous reports have shown the negative impact of low intake of calcium/dairy products on girls' trabecular bone after menarche.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(5) Therefore, an adequate intake of vitamin D during childhood and adolescence is necessary to enhance intestinal calcium absorption and ensure normal bone mineralization. (5) Several trials have investigated means to maximize peak bone mass through lifestyle measures, by increasing physical activity or emphasizing on dairy products consumption or supplementation of calcium and vitamin D. (1,(6)(7)(8)(9) Two randomized trials using calcium-fortified milk demonstrated increments in bone mass in adolescent Chinese girls and Gambian boys, but could not demonstrate residual effect after trial completion. (10,11) Our group had previously reported on the beneficial effects of vitamin D supplementation in adolescent girls, (12) but not boys, (13) on bone mineral content (BMC), bone mineral density (BMD), and lean mass, in a 1-year trial that compared two doses of vitamin D (low dose ¼ 200 IU/day; high dose ¼ 2000 IU/day) to placebo.…”
Section: Introductionmentioning
confidence: 99%